Output feedback stabilization for a Kirchhoff‐type nonlinear beam with general corrupted boundary observation - Guo, Wei; Chen, Yunlan; Feng, Hongyinping (International journal of robust and nonlinear control, 2017)
Summary This paper is concerned with the boundary output feedback stabilization for a Kirchhoff‐type nonlinear beam equation with boundary observation subject to a general disturbance. The active disturbance rejection control approach is adopted to design the controller and the disturbance estimator. By this approach, the disturbance is estimated by a relatively independent estimator and then canceled in the feedback loop. The existence and uniqueness of the classical solution to the closed‐loop system are proved. The asymptotical convergence of the closed‐loop system is obtained. Copyright © 2017 John Wiley & Sons, Ltd.